Distinct Claudin Expression Profiles of Hepatocellular Carcinoma and Metastatic Colorectal and Pancreatic Carcinomas - Holczbauer, Ágnes (SAGE Publications, 2013)
Tight junction proteins, including claudins, are often dysregulated during carcinogenesis and tumor progression. Moreover, the claudin expression pattern usually varies between different tumor entities. We aimed to investigate claudin expression profiles of primary and metastatic liver malignancies. We analyzed claudin-1, -2, -3, -4, and -7 expression by quantitative immunohistochemistry and real-time RT-PCR, respectively. Twenty hepatocellular carcinomas (HCCs) and liver metastases of 20 colorectal adenocarcinomas (CRLMs) and 15 pancreatic adenocarcinomas (PLMs) were studied together with paired surrounding non-tumorous liver samples and 5 normal liver samples. Strong claudin-3 and -7 immunohistochemical positivities were detected in CRLM samples, each with significantly stronger staining when compared with HCC and PLM groups. Claudin-1 protein was found highly expressed in CRLM, in contrast to lower expression in PLM and HCC. CRLMs and PLMs also were strongly positive for claudin-4, while being virtually undetectable in HCC. Claudin-2 showed strong positivity in non-tumorous liver tissue, whereas significantly weaker positivity was observed in all tumors. Differences in mRNA expression were mostly similar to those found by immunohistochemistry. In conclusion, HCC and both CRLM and PLM display distinct claudin expression profiles, which might provide better understanding of the pathobiology of these lesions and might be used for differential diagnosis.